Integration of Islamic Da’wah and Counseling Based on Social Media as an Effort to Overcome Student Problems - Widodo, M. Azka Nauval Madadi; Amanina, Annida Asma (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study aims to analyze the integration of da’wah and Islamic counseling based on social media as a holistic solution to the spiritual and psychological problems of students. The method used is library research with descriptive-interpretative analysis techniques. Data were obtained from literature sources such as scientific journals, books, and articles related to the research theme. The results of the study indicate that the integration of da’wah and counseling through digital platforms such as social media, chat applications, and specialized websites can address students’ needs for spiritual-psychological assistance that is accessible, contextual, and transformative. Service models proven to be effective include Islamic-based digital counseling, interactive da’wah sessions with counseling features, and integrative platforms that combine religious education and psychosocial support. The study’s conclusion emphasizes that this approach represents a modern actualization of the principle of Amar Ma’ruf Nahi Munkar while also serving as a strategic medium for guiding students in facing the challenges of the quarter-life crisis in the digital era.